PENGARUH PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP ETOS KERJA KARYAWAN PT.BANK MUAMALAT INDONESIA KC. DUMAI - Syarif, Willy; Samiatun, Samiatun (Journal Of Sharia Banking, 2024)
The realization of achieving work ethic targets has not been realized. This means achieving work targets at PT. Bank Muamalat Indonesia, Kc. Dumai has not been optimal and shows that employee work education is still lacking and employee work experience is also low. This is shown by not achieving employee work ethic targets. The formulation of the problem in this research is whether there is a partial and partial influence of education and work experience. simultaneously on the work ethic of employees at PT. Bank Muamalat Indonesia, Kc. Dumai. This research is quantitative research using primary data. The data collection instrument was carried out using a questionnaire. Sampling in this study used a non-probability sampling technique, namely a saturated sample with a sample size of 15 respondents taken from all members of the population, namely employees of PT. Bank Muamalat Indonesia, Kc. Dumai. The analysis tests used in this research are validity test, reliability test, normality test, classical assumption test, t test and f test using SPSS version 23. Based on the results of research and testing carried out using SPSS version 23, it shows that there is an influence education on the work ethic of employees at PT. Bank Muamalat Indonesia, Kc. Dumai. and work experience has no influence on the work ethic of employees at PT. Bank Muamalat Indonesia, Kc. Dumai. Meanwhile, the F test shows that there is an influence of education and work experience on the work ethic of employees at PT. Bank Muamalat Indonesia, Kc. Dumai.